Culture and professional training of psychologist in community work - Zamora, María Elena; Dimenstein, Magda; Vilhena, de, Junia (Revista de Psicología, 2000)
In this paper we start out with the assumption that identities are being constructed from the place the individual occupies inside his social and class context. Our purpose is to refelct on the impact of diversity of culture and professional training of psychologist, his practice, and the individuals of slum communities in Rio de Janeiro. The psychologist generally comes from teh Barzilian middle and high classes, where an individualistic ideal preodominates. Such individualistic culture and ideology are based on given idea and the psychologial model of "individual", is accepted as natural, applicable and extensible to all organizations and social classes. This corresponds in a general way to a person who thinks of itself as possessing citizenship, dignity, autonomy, ability to use its creative potencial, being able to formulate and verbalize inner problems and to think to himself as having freedom to control and manage his (hers) own life without further considerations on social determinations. Nevertheless, we are unable to find such system of ideas within the development of traditional, hierarchical and holistic societies, as is the case of slum populations. Such populations are characterized by more holistic system, of ideas, where community traditions and habits, reciprocity and solidarity nets condition individual existence. Such class cultural differences lie on cultural diversity between professionals and communities, which frequently results in interventions and strategies without populations. Some authors even mentionthe production, of real clinical "apartheid", and tend to see pathologies, negativity and essential faults where only cultural differences exist.